2009
DOI: 10.1002/jlcr.1670
|View full text |Cite
|
Sign up to set email alerts
|

[18F]/19F exchange in fluorine containing compounds for potential use in 18F‐labelling strategies

Abstract: Exchange of [18 F]fluoride with 19 F in various organofluorine compounds in concentrations ranging from 0.06 to 56 mM was explored. We aimed to explore whether exchange reactions can be a potential useful labelling strategy, when there are no requirement of high specific radioactivity. Parameters such as solvents, temperature, conventional vs microwave heating, and the degree of fluorine load in some aromatic and alkyl compounds were investigated with regard to radiochemical yield and specific radioactivity. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…The 19 F/ 18 F isotope exchange reaction was performed using relatively harsh conditions. The large substituent attached at the para position of the 1,2‐difluorobenzene ring of 1 reduces reactivity of the benzene ring and makes the isotope exchange reaction difficult, an outcome that has been demonstrated earlier with similar compounds . Using the present reaction conditions, we observed that the chemical decomposition of the precursor and also [ 18 F] 1 is rapid (Figure ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The 19 F/ 18 F isotope exchange reaction was performed using relatively harsh conditions. The large substituent attached at the para position of the 1,2‐difluorobenzene ring of 1 reduces reactivity of the benzene ring and makes the isotope exchange reaction difficult, an outcome that has been demonstrated earlier with similar compounds . Using the present reaction conditions, we observed that the chemical decomposition of the precursor and also [ 18 F] 1 is rapid (Figure ).…”
Section: Discussionsupporting
confidence: 76%
“…Previously, direct 19 F/ 18 F isotope exchange reactions have been applied to 18 F‐fluorination of small aromatic molecules. 18 F‐Labeling of larger molecules with 19 F/ 18 F isotope exchange reaction has been reported to be more difficult, and commonly, these molecules have been produced with at least a two‐step synthesis where protecting groups were needed or by coupling a 18 F‐labeled small molecule with a larger molecule . In this study, [ 18 F] 1 was synthesized using one‐step synthesis and 19 F/ 18 F isotope exchange reaction (Figure ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even more remarkable is that this reaction reaches equilibrium within seconds. Fluorine exchange in organic compounds has been reported before 15 , however, to our knowledge this is the first example of fluoride exchange of a C-F bond in a heterocyclic compound.…”
mentioning
confidence: 79%
“…The published radiosynthesis of 18 F-HFB (Figure 2) 13 was adapted for automation on a modular system (Eckert and Ziegler). The synthesis was conducted at room temperature (RT) in dimethyl sulfoxide (DMSO) and quantities of K 2 CO 3 , K 2.2.2 , and HFB were adjusted in order to achieve good yields using the lowest amount of HFB (Table 1).…”
mentioning
confidence: 99%